2021
DOI: 10.1111/odi.13811
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide DNA methylation changes in oral submucous fibrosis

Abstract: Objective Oral submucous fibrosis (OSF) is a debilitating potentially malignant condition of the buccal cavity characterized by extensive extracellular matrix deposition resulting in stiffness and trismus. As OSF is a progressive disease, we hypothesized that there would be extensive epigenetic changes in OSF tissues. Materials and Methods Using the Infinium HumanMethylation450 BeadChip Array, we analyzed gross DNA methylation changes in seven OSF tissues compared to five controls. Comparison with transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…10 Paramita Kundu et al found that the transcript for XIST located on the X chromosome was downregulated due to hypermethylation of the XIST promoter in OSF tissues. 6 Xu et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Paramita Kundu et al found that the transcript for XIST located on the X chromosome was downregulated due to hypermethylation of the XIST promoter in OSF tissues. 6 Xu et al…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that SMAD2/3 promotes binding of the m6A methyltransferase METTL3–METTL14 complex to a subset of transcripts involved in early cell fate decisions 10 . Paramita Kundu et al found that the transcript for XIST located on the X chromosome was downregulated due to hypermethylation of the XIST promoter in OSF tissues 6 . Xu et al found that methylation of CpG islands in E‐cadherin and COX‐2 occurred frequently in patients with OSF 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these molecular events could also play oncogenic roles in other oral, potentially malignant disorders, such as proliferative verrucous leukoplakia, where the presence of a band-like lymphocytic chorionic infiltrate constitutes an unspecific histopathologic feature affecting up to 30% of patients [ 49 ]. Furthermore, increased levels of cytokines (e.g., interleukin-6 and tumour necrosis factor alpha) have also been reported in patients with oral lichen planus [ 50 ], oral submucous fibrosis [ 51 ] and oral leukoplakia [ 52 ]. In head and neck cancer, as previously mentioned, inflammation is a well-established hallmark, and numerous oncogenic mechanisms have been documented [ 39 ], e.g., the infiltration of inflammatory cells facilitating tumour development through the regulation of growth factors from mitogenic signalling pathways [ 53 ], the attenuation of the host immune response to tumour cells [ 54 ], or the determination of cytokines and chemokines playing key roles by promoting angiogenesis, proliferation and the immune cell response [ 55 , 56 , 57 ].…”
Section: Sp/nk1r In Head and Neck Mucosal Inflammation And Cancermentioning
confidence: 99%